OBSTACLES PREVENTING HIGH ACHIEVERS FROM LOW SOCIOECONOMIC BACKGROUNDS TO ENTER UNIVERSITIES: A REVIEW - Chieng Yen Yun; Muhammad Asyraf Che Amat; Zeinab Zaremohzzabieh, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
All students, regardless of socioeconomic status, deserve equitable access to universities. However, many high-achieving students are excluded from this privilege, most of whom come disproportionately from families on the lower rungs of the socioeconomic ladder. This study aims to identify the barriers that influence high achievers from disadvantaged socioeconomic backgrounds to pursue higher education. A total of ten relevant articles from prominent publication databases were chosen for this review. The results show that the majority of researchers believe that parents' negative attitudes, parents' low expectations, first-in-family, vogue career identity, financial factor, and thinking style factor are the primary impediments to high achievers from disadvantaged socioeconomic backgrounds attending university. The results also enable university career counsellors to assist high achievers from disadvantaged socioeconomic backgrounds to overcome any obstacles to effectively join universities and fulfil their educational goals.